DESAIN LOGO DAN MEDIA PROMOSI INSTAGRAM SEBAGAI CITRA PRODUK MAKANAN UMKM RISOLES DAN CATERING - Firmansyah, Yoga Dwi; Febriana, Poppy; Rochmaniah, Ainur (Jurnal Abdi Insani, 2024)
Industrial development in Indonesia, which increases every year, has a significant impact on MSME players. MSME players must have characteristics that are different from other businesses. The Community Service Team assisted 1 MSME actor who has 2 types of business, namely Risoles & Catering, with the problem of not having a logo and an Instagram social media account to promote their products. The community service team provides assistance to MSME Risoles & Catering players with the aim of ensuring that MSME players can have a permanent logo and have an Instagram account as promotional media which has an impact on optimizing sales. In this service, there are 4 method stages. The stages used are the Observation, Implementation, Supervision and Evaluation stages. At this stage, this method becomes a supporting factor for continuity in the service that will be carried out. The results of this assistance ran smoothly and had a positive impact on the MSME Catering and Risol players. Both types of MSMEs already have a permanent logo which is the characteristic of their products for the continuity of product sales, have official Instagram social media accounts @Cateringmak_ and @Risolmak_. Users of the @Cateringmak_ and @Risolmak_ accounts already have less than 50 followers per account, which can be assessed by the outside public as knowing the products sold by both types of MSMEs. Both MSMEs already have Instagram feed designs as promotional media that have an impact on optimizing sales through social media. The conclusion from community service is that promotion of Instagram social media and logos is one of the keys to optimizing sales of MSME products.